Usefulness of the Hybrid RFR-FFR Approach: Results of a Prospective and Multicenter Analysis of Diagnostic Agreement between RFR and FFR—The RECOPA (REsting Full-Cycle Ratio Comparation versus Fractional Flow Reserve (A Prospective Validation)) Study - Juan Casanova-Sandoval; Diego Fernández-Rodríguez; Imanol Otaegui; Teresa Gil Jiménez; Marcos Rodríguez-Esteban; Kristian Rivera; Francisco Torres-Saura; Víctor Jiménez Díaz; Raymundo Ocaranza-Sánchez; Vicente Peral Disdier; Guillermo Sánchez-Elvira; Fernando Worner (Journal of Interventional Cardiology)
Background. The resting full‐cycle ratio (RFR) is a novel resting index which in contrast to the gold standard (fractional flow reserve (FFR)) does not require maximum hyperemia induction. The objectives of this study were to evaluate the agreement between RFR and FFR with the currently recommended thresholds and to design a hybrid RFR-FFR ischemia detection strategy, allowing a reduction of coronary vasodilator use. Materials and Methods. Patients subjected to invasive physiological study in 9 Spanish centers were prospectively recruited between April 2019 and March 2020. Sensitivity and specificity studies were made to assess diagnostic accuracy between the recommended levels of RFR ≤0.89 and FFR ≤0.80 (primary objective) and to determine the RFR “grey zone” in order to define a hybrid strategy with FFR affording 95% global agreement compared with FFR alone (secondary objective). Results. A total of 380 lesions were evaluated in 311 patients. Significant correlation was observed (R2 = 0.81; P<0.001) between the two techniques, with 79% agreement between RFR ≤ 0.89 and FFR ≤ 0.80 (positive predictive value, 68%, and negative predictive value, 80%). The hybrid RFR-FFR strategy, administering only adenosine in the “grey zone” (RFR: 0.86 to 0.92), exhibited an agreement of over 95% with FFR, with high predictive values (positive predictive value, 91%, and negative predictive value, 92%), reducing the need for vasodilators by 58%. Conclusions. Dichotomous agreement between RFR and FFR with the recommended thresholds is significant but limited. The adoption of a hybrid RFR-FFR strategy affords very high agreement, with minimization of vasodilator use.